The Importance of Implementing a Creativity Program for Students at Inclusion Schools - Nabilah, Nabilah; Larasati, Lionifa Kurnia; Fauzi, Muhammad Allen Nur; Ilhami, Nadif Ramadhan (Universitas Sebelas Maret, 2024)
Creativity must be developed in the right way to enhance quality and self-confidence. For students with special needs, this is useful to dispel negative assumptions from the surrounding environment, which can impact their mental development. The Creative Education Program (CEP) holds potential as a solution to assist students in schools. The findings of this study include: (1) CEP is a training program organized by schools to prioritize the creative process so that students can absorb lessons effectively and become more interested in learning; (2) The implementation of CEP has been carried out in several elementary schools, namely SLB Bina Harapan, SLB Negeri 1 Bantul, and SLB PGRI Prembun; (3) The benefits of CEP include the development of critical and innovative thinking skills, the nurturing of special interests and talents, and the enhancement of interpersonal skills; (4) CEP is crucial to be implemented in inclusive schools that have not yet incorporated creativity programs directly into children's education.